Intramolecular electron-induced proton transfer and its correlation with excited-state intramolecular proton transfer - Wei Wang (Nature Portfolio, 2019)
Intramolecular electron-induced proton transfer (iEIPT) describes proton motion coupled with the attachment of an electron within a molecule. Here, the authors build a “search engine” for iEIPT-capable molecules that also have the excited-state intramolecular proton transfer property.